Simulation of the forming of tufted multilayer composite preforms. (1st September 2021) - Huang, Jin; Boisse, Philippe; Hamila, Nahiène
Abstract: Tufting of preforms increases the resistance of the laminated composites to delamination. Draping of the preforms is clearly modified by the presence of tufting threads. A simulation approach for the forming of tufted textile reinforcement stacks is proposed. It determines the state of the tufted preforms after forming and in particular the possible wrinkles. The layers of textile reinforcements are modeled by stress resultant shells. Tufting threads are modeled by rod chains that can slide with friction relative to the textile reinforcements. The geometry of these rod elements is enhanced by a description of Hermite and the bending of the threads is taken into account through the position of neighboring elements. The approach accurately simulates the forming of tufted preforms and in particular the wrinkles that are observed in the forming experiments.